Time Use in Domestic Settings Throughout the Life Course The Italian Case - Dotti Sani, Giulia Maria (SpringerBriefs in Sociology,, 2018)
The volume is the first to take a life-course approach to the study of domestic work in Italy. It provides a coherent and systemic overview of time spent on housework, childcare and adult care over the life course. While most previous research has focused on the time adult women and men spend on housework and the division of domestic chores among partners, this unique contribution studies the amount of time spent on chores by Italians in different phases of the life course. It addresses relevant aspects often neglected in time use studies, such as the socialization to domestic chores among children, teenagers and young adults living in the parental home and the reproduction of gender inequalities in housework at later stages of the life course.